2010
DOI: 10.1590/s1983-14472010000200015
|View full text |Cite
|
Sign up to set email alerts
|

Implantação do diagnóstico de enfermagem em unidade de terapia intensiva: uma análise periódica

Abstract: RESUMOO conhecimento acerca da prevalência dos diagnósticos de enfermagem (DE) contribui para a previsão dos cuidados necessários e para a orientação de programas de educação permanente. Estudo com delineamento transversal, que teve por objetivo identificar os principais DE de uma unidade de terapia intensiva (UTI), comparando-se as diferentes categorias entre os pacientes clínicos e cirúrgicos. A análise dos dados foi realizada de acordo com a taxonomia II da North American Nursing Diagnoses Association (NAND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 13 publications
1
9
1
14
Order By: Relevance
“…The prevalence of males in the studied population was also found in other studies (10) ; female predominance was found among the patients of other Intensive Care Units studied (11)(12)(13) , with a small difference between the percentages, showing some equality between the genders. Regarding the age group, it was found an even higher percentage of patients aged ≥60 years, 68.3% (14) .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The prevalence of males in the studied population was also found in other studies (10) ; female predominance was found among the patients of other Intensive Care Units studied (11)(12)(13) , with a small difference between the percentages, showing some equality between the genders. Regarding the age group, it was found an even higher percentage of patients aged ≥60 years, 68.3% (14) .…”
Section: Discussionsupporting
confidence: 84%
“…Among the diagnoses found, 49.0% were considered risk diagnoses, indicating a high concern not only with problems already installed, but also with potential problems. The mean of 7.5 diagnoses per patient was an intermediate value when compared to other similar studies that found averages equal to 19.4 (15) , 8.5 (14) and 1.3 (10) .…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…No presente estudo verificou-se que a faixa etária dos participantes variou entre 18 a 83 anos, sendo que 17,5% apresentaram idade entre 18 a 28 anos, 35% tinham entre 29 a 39 anos e 47,5% eram pacientes com idade de 40 anos ou mais. Estudos semelhantes, realizado em 2007, por Paganim et al(2010)19 com uma amostra de 150 prontuários de um hospital público da serra gaúcha, mostra que a maioria dos pacientes também eram do sexo masculino (60,7%) e outro estudo conduzido porFeijó et al (2006) 20 com pacientes do Hospital Elaboração própria estudo, sendo descritos conforme a publicação atual da classificação dos diagnósticos de enfermagem da Taxonomia II da NANDA-I. Assim, verificou-se um total de 21 diagnósticos, sendo que 10 apresentaram frequência ≥ 70%.…”
unclassified